Real time drilling mud gas response to small-moderate earthquakes in Wenchuan earthquake Scientific Drilling Hole-1 in SW China. (1st May 2017) - Gong, Zheng; Li, Haibing; Tang, Lijun; Lao, Changling; Zhang, Lei; Li, Li
Graphical abstract: Highlights: Regional aftershocks have a major impact on the drilling mud behavior. Mud gas variations are likely triggered by dynamic stress. High hydraulic diffusivity and limited source inhibit the gas responses. Abstract: We investigated the real time drilling mud gas of the Wenchuan earthquake Fault Scientific Drilling Hole-1 and their responses to 3918 small-moderate aftershocks happened in the Longmenshan fault zone. Gas profiles for Ar, CH4, He, 222 Rn, CO2, H2, N2, O2 are obtained. Seismic wave amplitude, energy density and static strain are calculated to evaluate their power of influence to the drilling site. Mud gases two hours before and after each earthquake are carefully analyzed. In total, 25 aftershocks have major mud gas response, the mud gas concentrations vary dramatically immediately or minutes after the earthquakes. Different gas species respond to earthquakes in different manners according to local lithology encountered during the drill. The gas variations are likely controlled by dynamic stress changes, rather than static stress changes. They have the seismic energy density between 10 −5 and 1.0 J/m 3 whereas the static strain are mostly less than 10 −8 . We suggest that the limitation of the gas sources and the high hydraulic diffusivity of the newly ruptured fault zone could have inhibited the drilling mud gas behaviors, they are only able to respond to a small portion of the aftershocks. This work is important for the understanding of earthquake related hydrological changes.